Service Quality and Unmet Need for Family Planning in Childbearing-Age Women at Jambesari Darus Sholah Sub-District, Bondowoso Regency - Aulia, Dinda Masitha; Ramani, Andrei; Baroya, Ni'mal (Unnes Journal of Public Health, 2020)
The unmet need for family planning in Bondowoso Regency is the third highest in East Java. Jambesari Darus Sholah Subdistrict is the sub-district with the highest number of unmet needs in Bondowoso Regency. This study aims to analyze the relationship of service quality with unmet need for family planning in Jambesari Darus Sholah District, Bondowoso Regency. This was an analytic study with cross sectional design. The sample of this research was 149 married women who were selected by simple random sampling technique. Collecting data of this study through structured interview methods using a questionnaire. Data analysis used chi-square test and logistic regression test with backward method with a significance level of 95%. The results showed that respondents who experienced unmet need for family planning were 20.1%. If reviewed based on the type of unmet need for family planning, 83.3% do not want more children and 16.7% want children to be postponed. Women who are older, have children > 2 and have low education are at greater risk of unmet need for family planning. The quality of family planning services was related to unmet need for family planning. Women who receive poor quality family planning services are at risk of unmet need for family planning 3.3 times greater than good quality family planning services. Thus, increasing the quality of family planning services becomes important to reduce the number of unmet needs for family planning.